2023
DOI: 10.1001/jamaoto.2022.4107
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Monitoring of Circulating Tumor HPV DNA in HPV-Associated Sinonasal and Nasopharyngeal Cancers

Abstract: This prospective observational study examines if circulating tumor human papillomavirus DNA can be used as an accurate measure of disease status at the time of diagnosis, throughout treatment, and during monitoring in human papillomavirus-associated sinonasal and nasopharyngeal squamous cell carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Zupancic and Näsman performed a systematic review and found that 77 of 79 (97.5%) cases of HPV-related multiphenotypic sinonasal carcinoma occurred within the sinonasal cavity with no regional metastasis, while one occurred in the breasts, and one in the tonsils [61] . Additionally, given that approximately one-third of SNSCCs are HPV-associated [62] , circulating HPV DNA (ctHPVDNA) is being investigated as a noninvasive biomarker of disease status both at diagnosis and throughout treatment [63] . Studies have demonstrated that HPV-associated SNSCC may have genotype distributions distinct from HPV+ oropharyngeal carcinoma, with HPV 16 being less common [64] .…”
Section: Pet/ctmentioning
confidence: 99%
“…Zupancic and Näsman performed a systematic review and found that 77 of 79 (97.5%) cases of HPV-related multiphenotypic sinonasal carcinoma occurred within the sinonasal cavity with no regional metastasis, while one occurred in the breasts, and one in the tonsils [61] . Additionally, given that approximately one-third of SNSCCs are HPV-associated [62] , circulating HPV DNA (ctHPVDNA) is being investigated as a noninvasive biomarker of disease status both at diagnosis and throughout treatment [63] . Studies have demonstrated that HPV-associated SNSCC may have genotype distributions distinct from HPV+ oropharyngeal carcinoma, with HPV 16 being less common [64] .…”
Section: Pet/ctmentioning
confidence: 99%
“…1,2 For example, the incidence of oropharyngeal cancer has now exceeded that of cervical cancer in the United States, in part due to the rise of HPV-driven pathology. 1,3 HPV-associated head and neck tumors most commonly occur in the oropharynx, with the second most common site being the sinonasal tract. Currently known HPV-driven pathology in the nasopharynx and sinuses includes nasopharyngeal carcinoma (NPC), sinonasal squamous cell carcinoma (SNSCC), sinonasal papillomas, a few subtypes of neuroendocrine carcinomas, among many others.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating tumor DNA (ctDNA) has emerged as an accurate real-time biomarker of disease status across most solid tumor types [2][3][4][5][6][7][8] . However, the performance metrics of ctDNA for detecting MRD immediately following surgery remain poorly understood, due to the scarcity of data available, variability in the approaches used, and the difficulty correlating MRD with recurrence when adjuvant treatment is delivered.…”
Section: Introductionmentioning
confidence: 99%